"Advanced materials" and the challenges on the horizon for testing their (eco)toxicity and assessing their hazard. Issue 2 (12th January 2023) - Abdolahpur Monikh, Fazel; Peijnenburg, Willie; Oomen, Agnes G.; Valsami-Jones, Eugenia; Stone, Vicki; Kortet, Raine; Akkanen, Jarkko; Zhang, Peng; Kekäläinen, Jukka; Sevcu, Alena; Kukkonen, Jussi V. K.
Abstract : "Advanced Materials" (AdMas) represent the next technology frontier. Abstract : "Advanced Materials" (AdMas) represent the next technology frontier. According to the European Union, AdMas are materials that feature a series of exceptional properties or functionalities compared to conventional materials. Considering the progress made in the design and application of AdMas, their adverse effects are still largely unknown whilst this is critical for assessing their environmental and human health risk. In this perspective, we first summarize the available definitions/descriptions and categorizations that cover AdMas and evaluate their adequacy from a toxicological point of view. We further describe the challenges and outlook on the toxicology of AdMas and propose solutions to tackle some of the challenges. Criteria related to which AdMas might induce hazards are discussed and used to propose a starting point of how to address AdMas in legal frameworks that consider human and environmental risks. Finally, we highlight the benefit of classification, e.g., enabling differentiation between AdMas based on their properties that might induce specific hazards and facilitate a faster pathway to identify the hazards of new AdMas, which is particularly relevant for safe-by-design.